Ending a sponsorship relationship: consumers' responses toward a forced versus a chosen exit. Issue 2 (15th March 2017) - Dick, Christopher; Uhrich, Sebastian
ABSTRACT: Research question: Sponsorship relationships can be categorized into a beginning, an ongoing, and an ending phase. Although all of these phases can be consequential for the sponsoring brand, past research mainly focuses on the beginning phase and the management of existing sponsorships, and only a few studies examine the effects of ending a sponsorship relationship. The present study addresses this gap by exploring how two types of exit (chosen vs. forced) and the exit consequences (few vs. extensive) influence consumers' evaluations of the sponsor brand. Research methods: This research uses an experimental study ( N = 202). Data were collected among supporters of a German second division soccer team. Results and findings: The results reveal that consumers' attitudes are negatively affected when the sponsor's exit is freely chosen (vs. forced). These effects are moderated by the exit's consequences. The detrimental effect of a chosen exit is particularly strong when the exit has extensive (vs. few) negative consequences for the sponsored property. The findings further show that the interaction of the type of exit (chosen vs. forced) and the exit's consequences on consumers' attitudes is mediated by the perceived abandonment of the sponsored property. Implications: We contribute to the literature by expanding knowledge about the effects of a sponsorship termination on consumers' attitudes toward the sponsor brand. The present study highlights the effects of different types of exit on consumers' attitudes and identifies the explanatory mechanisms underlying these effects. Furthermore, our research offers several practical recommendations regarding the management of sponsorship termination.